Intraoperative risk factors associated with the need for reintervention in free flaps: a retrospective study in a third-level referral center in Mexico (2022-2025) - Roldán, Luis E.; Ramírez, Eduardo D.; C. Guadarrama, Daniel; Ugalde, Juan A.; F. Riera, Ricardo (International Journal of Research in Medical Sciences, 2026)
Background: Free flap surgery is the gold standard for complex reconstruction, yet vascular compromise requiring reintervention remains a significant challenge. This study aims to identify intraoperative risk factors associated with take-back procedures at the Hospital General de México "Dr. Eduardo Liceaga." Methods: A retrospective comparative study of 121 patients undergoing free flap reconstruction (2022–2025) was conducted. Demographic data, flap types, and intraoperative variables were analyzed. Patients were divided into two groups: Reintervened (n=41) and non-reintervened (n=80). Statistical significance was set at p<0.05. Results: The reintervention rate was 33.8%. The DIEP flap was the most common (26.45%). Younger age was significantly associated with reintervention (32 vs 46 years; p=0.004). The use of intraoperative vein grafts was a major risk factor, present in 29.27% of reintervened cases versus 10% in the successful group (p=0.01). Ischemia time and type of anastomosis did not show statistical significance. Conclusions: In our population, younger age and the primary need for vein grafts are critical predictors of reintervention. These findings emphasize the need for specialized monitoring protocols for these high-risk subgroups in high-volume Mexican institutions.